Modelling of the milk supplied to the industry in Turkey through Box-Jenkins and Winters' Exponential Smoothing methods - Akın, Ahmet Cumhur; Tekindal, Mustafa Agah; Arıkan, Mehmet Saltuk; Çevrımlı, Mustafa Bahadır (My University, 2020)
Analysis of the quantity of cow milk supplied to the industry in Turkey is one of the methods that could providestakeholders with the most accurate results from the perspective of raw milk projections and the interpretation of thesector. Therefore, it is important that the amount of milk supplied to the industry is used instead of the total amount ofmilk produced in the projections of the sector. The present study is intended to model the time series data of the amountof milk supplied to the dairy industry in Turkey between 2013/01 and 2018/03 using Box-Jenkins and Winters'Exponential Smoothing methods, and to analyse the production of milk and the future of the dairy industry in Turkeyutilising the forecasts obtained from such models. The results of the analyses indicate that the Winters' ExponentialSmoothing model gives more consistent results than the Box-Jenkins model with respect to the future forecast value anddecision-making criterion of the amount of milk supplied to the industry.
Keywords: Beslenme ve Diyetetik; Veterinerlik; İstatistik ve Olasılık